PROBLEMS FACED BY SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN MASTERING SPEAKING SKILL IN 2008/2009 ACADEMIC YEAR - SURONO , SURONO (2010)
The research studies about the problems faced by the second semester students of English department of Muhammadiyah university of Surakarta and the learning strategies to improve speaking skill. The subject of this research is second semester students of English department of Muhammadiyah university of Surakarta In this research the data are derived from interview, observation and document. There are there techniques in collecting the data, namely: observation, interview, and documentation. The researcher uses the descriptive qualitative in analyzing the data. The result of the research shows that there are seven problems in mastering speaking skill, namely: limited vocabulary, pronunciation, material, listening skill/ understanding, grammar, fluency/ accuracy, anxiety. The result of this research shows that the there of the subjects use almost all of the learning strategies proposed by O'malley and Chamot. However their action and attention in learning are different. S uses 7 learning strategies there are: Resourcing, Repetition, Elaboration, Management Strategies, Question and Clarification, Advance Organizer, Socio affective Strategies. And F uses 6 learning strategies there are: Resourcing, Repetition, Question and Clarification, Advance organizer, Socio Affective Strategies, Selective attention. And M uses 6 learning strategies there are: Resourcing, Repetition, Cooperation Strategies, Directive Attention, Self Management, Socio Affective.